2018
DOI: 10.1080/13636820.2018.1549092
|View full text |Cite
|
Sign up to set email alerts
|

Identifying motivational profiles among VET students: differences in self-efficacy, test anxiety and perceived motivating teaching

Abstract: There are indicators that a substantial number of students in vocational education and training (VET) experience problems with successfully building their careers. This is often attributed to VET students' motivation. The present study provides insight into VET students' motivational profiles based on selfdetermination theory. Additionally, differences between those motivational profiles in terms of self-efficacy, test anxiety and perception of motivating teaching were investigated. The study involved 195 VET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…This indicates that online and classroom VET students perceived the value of the task -the course they enrolled on-to be equally important, even though task value has been proven to be one of the most important motivational factors, it being associated with learning engagement and success (Aristeidou et al, 2017;Zhang and Liu, 2019) and a significant predictor of course completion (Cho and Heron, 2015;Vanslambrouck et al, 2018). As Cents-Boonstra et al (2018) showed, VET students with a higher level of motivation also have a higher level of self-efficacy, which is strongly linked to learning success.…”
Section: Identifying Differences Between Learning Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that online and classroom VET students perceived the value of the task -the course they enrolled on-to be equally important, even though task value has been proven to be one of the most important motivational factors, it being associated with learning engagement and success (Aristeidou et al, 2017;Zhang and Liu, 2019) and a significant predictor of course completion (Cho and Heron, 2015;Vanslambrouck et al, 2018). As Cents-Boonstra et al (2018) showed, VET students with a higher level of motivation also have a higher level of self-efficacy, which is strongly linked to learning success.…”
Section: Identifying Differences Between Learning Modesmentioning
confidence: 99%
“…Several researchers have suggested (e.g., Cardinal, 2010;Cents-Boonstra et al, 2018;Dubeau et al, 2017;Biemans et al, 2019) that VET programs attract less motivated students, and studies on VET motivational and SRL strategies are therefore not priority areas for exploration. To us, this opens a door to new research, which might focus on the Catalan context using the preliminary validated scales to compare motivation levels and SRL strategies between VET and high-school or university students-these being similar in age but differing in levels of motivation (Martin, 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To comply with the challenge of recruiting more people for teacher training to overcome the above-mentioned lack, we need to know where and how to find further potential applicants. One important angle to consider on that note are the motives why students chose the profession of vocational education and training (VET) teacher in the first place (Driesel-Lange et al, 2017). However, their career choice motivation-understood as the factors or reasons that are influential for the decision to choose teaching as a career (Han & Yin, 2016;Thomson et al, 2012;Watt et al, 2012;Wenström et al, 2018)-is little studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles in this issue examine psychological aspects related to the motivation of 16þ-year old students in vocational education settings. Studies have reported motivational problems of students in vocational education, yet there is little research on this topic (Cents-Boonstra et al, 2019;Glerum et al, 2018). Therefore, the investigation of students' motivation in a vocational context is essential.…”
Section: Editorialmentioning
confidence: 99%